Peningkatan Perekonomian Masyarakat Desa Sinar Harapan Melalui Inovasi Produk Olahan Buah Pala Dan Pemasaran Berbasis Digital Pada UMKM Pala Sari - Khaidarmansyah k; Nisar N (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2026)
This community service activity aims to improve the economic conditions of the Sinar Harapan Village community through innovation in nutmeg-based products and the implementation of digital marketing for UMKM Pala Sari. The main problems faced by the partner include low product durability, unattractive packaging, and limited conventional marketing reach. The method used consists of preparation, product quality improvement training, packaging design, and digital marketing implementation through marketplaces. The results indicate improvements in product quality, enhanced packaging design, and expanded market reach to the national level. Additionally, this activity has increased community skills in business management and information technology utilization. Therefore, this program contributes to the sustainability of UMKM and improves the welfare of rural communities.